2023
DOI: 10.1371/journal.pdig.0000260
|View full text |Cite
|
Sign up to set email alerts
|

Predicting HIV infection in the decade (2005–2015) pre-COVID-19 in Zimbabwe: A supervised classification-based machine learning approach

Abstract: The burden of HIV and related diseases have been areas of great concern pre and post the emergence of COVID-19 in Zimbabwe. Machine learning models have been used to predict the risk of diseases, including HIV accurately. Therefore, this paper aimed to determine common risk factors of HIV positivity in Zimbabwe between the decade 2005 to 2015. The data were from three two staged population five-yearly surveys conducted between 2005 and 2015. The outcome variable was HIV status. The prediction model was fit by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
0
1
0
Order By: Relevance
“…Some studies have also used machine learning models to predict the spread of HIV in the AIDS pandemic, and the collected research factors are similar to those in this study, such as patient age, marital status, type of residence, occupation and route of HIV infection. The authors used these research factors to establish machine learning models to predict AIDS transmission, and the research results also showed that the XGboost model is the best algorithm to predict HIV status, which can help identify people who may need pre-exposure prophylaxis and is more helpful for the detection of socio-behavioral HIV [25] .…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have also used machine learning models to predict the spread of HIV in the AIDS pandemic, and the collected research factors are similar to those in this study, such as patient age, marital status, type of residence, occupation and route of HIV infection. The authors used these research factors to establish machine learning models to predict AIDS transmission, and the research results also showed that the XGboost model is the best algorithm to predict HIV status, which can help identify people who may need pre-exposure prophylaxis and is more helpful for the detection of socio-behavioral HIV [25] .…”
Section: Discussionmentioning
confidence: 99%
“…The study reveals that MLP performed better in predicting STIs among MSM with a high accuracy of 87.54%, recall of 97.29%, precision of 89.64%, F1-Score of 93.31% and AUC of 66.78%. Other studies, including one by Birri Makota and Musengi [ 14 ] also applied different HIV prediction models and XGBoost outperformed other models. With such good performance, these models can be effectively used to develop pre-test STI infection screening tools to identify highly at-risk individuals within the MSM community [ 2 ] and prioritise resource allocation to improve the health outcomes of these hard-to-reach communities.…”
Section: Discussionmentioning
confidence: 99%
“…The findings of their study found that the Farrington models performed better than the catalytic models. Furthermore, Birri Makota and Musenge (2023) [ 14 ] also applied the XG Boost algorithm to predict HIV status in Zimbabwe using Demographic Health Survey data from 2005 to 2015. Their study revealed that XGBoost performed better than other models on original data and SMOTE-balanced data.…”
Section: Related Workmentioning
confidence: 99%